Survei Manajemen Event Festival Olahraga Daerah Ke Ii Kormi Jawa Timur Tahun 2024 di Kota Surabaya - Wildan Rizqi Agustian; Andun Sudijandoko; Made Pramono; A. Burhanuddin Kusuma Nugraha (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Regional Sports Festival (FORDA) II KORMI East Java is a Community Sports Festival where this event is held every 2 years, the organizer of this event itself is the Indonesian Community Sports Committee (KORMI) East Java Province assisted by the organizing committee from KORMI City/Regency who is the host. The purpose of holding this event is as a preparation for the National Sports Festival (FORNAS) for the implementation of FORNAS VIII itself, God willing, it will be held at the end of June to the beginning of July in West Nusa Tenggara. FORDA II itself was attended by 37 Parent Sports Organizations (INORGA) from 34 KORMI Cities/Regencies in East Java Province, the number of participants participating in this activity was 3,678 participants with the following details: 3,162 activists, 292 officials and 224 coaches.